2004
DOI: 10.1063/1.1667612
|View full text |Cite
|
Sign up to set email alerts
|

Room-temperature saturated ferroelectric polarization in BiFeO3 ceramics synthesized by rapid liquid phase sintering

Abstract: Single-phased ferroelectromagnet BiFeO3 ceramics with high resistivity were synthesized by a rapid liquid phase sintering technique. Saturated ferroelectric hysteresis loops were observed at room temperature in the ceramics sintered at 880 °C for 450 s. The spontaneous polarization, remnant polarization, and the coercive field are 8.9 μC/cm2, 4.0 μC/cm2, and 39 kV/cm, respectively, under an applied field of 100 kV/cm. It is proposed that the formation of Fe2+ and an oxygen deficiency leading to the higher leak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
380
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,023 publications
(400 citation statements)
references
References 11 publications
13
380
7
Order By: Relevance
“…However, beside these potential applications of BFO, there are some serious problems, such as high leakage current arising from impurities, defects or non-stoichiometry (Wang et al 2004;Park et al 2007). Its remnant magnetization (M r ) and potential magnetoelectric effect both vanish on a macroscopic scale, giving rise to a quadratic ferromagnetoelectric behavior rather than a linear ferromagnetoelectric behavior (Fiebig 2005;Eerenstein et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, beside these potential applications of BFO, there are some serious problems, such as high leakage current arising from impurities, defects or non-stoichiometry (Wang et al 2004;Park et al 2007). Its remnant magnetization (M r ) and potential magnetoelectric effect both vanish on a macroscopic scale, giving rise to a quadratic ferromagnetoelectric behavior rather than a linear ferromagnetoelectric behavior (Fiebig 2005;Eerenstein et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the requirement of nanosized oxides and in order to avoid bismuth volatilization the developing of low temperature synthesis methods is essential. Previous studies have demonstrated that synthesis of bismuth Ferrites nanoparticles through a traditional solid-state method produces poor reproducibility and causes formation of coarser powders as well as Bi 2 O 3 /Bi 2 Fe 4 O 9 and other impurity phases [8,9], however, these approaches have certain short comings such as impurities in the final products [10]. S.Ghosh et al [11], used low temperature synthesis of bismuth ferrite nanoparticles by a ferrioxalate precursor method, the synthesis route is simple, energy saving and cost-effective, this work showed that the reaction of Bi 2 O 3 and Fe 2 O 3 results in the formation of multiphase products.…”
Section: I-introductionmentioning
confidence: 99%
“…BFO powders have been prepared by the solid-state methods [2,3] and mechano-chemical ones [4] and solution chemistry methods such as precipitation / coprecipitation [5], sol-gel [6,7], alkali metal ions-assisted controllable synthesis hydrothermal method [8] and sonochemical ones [9]). Most of the mentioned procedures need high temperature treatments (>800°C).…”
Section: I-introductionmentioning
confidence: 99%
“…species to Fe 2? and in oxygen vacancies for charge compensation (Wang et al 2004;Martin 2010;Cheong and Mostovoy 2007). The preparation of single-phase BFO without impurities is a critical task due to its narrow temperature stability range (Jaiswal et al 2010 (b) In general, the platinum crucible is needed for its preparation, which can be used only for three or four times.…”
Section: Introductionmentioning
confidence: 99%